Novosti pri terapevtskem spremljanju koncentracij vankomicina - Nadrah, Kristina (Zdravniški vestnik, 2011)
Vancomycin is a glycopeptide antibiotic used for treatment of infections caused by methicillinresistant Staphylococcus aureus (MRSA). During the last decade there have been reports of glycopeptide-resistant strains of Staphylococcus aureus. In some cases there are heterogenous populations of glycopeptide-susceptible and resistant strains which cannot be differentiated by standard clinical microbiology methods, but cause treatment failure and cross-resistance to other antibiotics. In order to improve clinical successanddiminish the occurence of resistance, vancomycin trough concentrations of 15-20 mg/L have been recommended. With such high trough concentrations there have been warnings and doubts about the nephro-and ototoxicity of vancomycin. The review article describes new guidelines for therapeutic monitoring of vancomycin concentrations and the scientific background of the amendments. We discuss the pharmacokinetic and pharmacodynamic characteristics of vancomycin, its toxicity and the problem ofresistance.
Keywords: farmakokinetika; stafilokokne infekcije; therapy; vankomicin; zdravljenje